The Impact and Management of Gynaecomastia in Klinefelter Syndrome - Raheem, Amr Abdel; Zaghloul, Ahmed Said; Sadek, Ahmed M. G.; Rayes, Bilal; Abdel-Raheem, Tarek M. (Frontiers in Reproductive Health, 2021)
Gynecomastia is defined as a palpable enlargement of the male breast, secondary to an increase in the glandular and stromal breast tissue. Gynecomastia is encountered in up to 80% of Klinefelter syndrome cases. The pathophysiology involves testosterone/oestrogen imbalance. This review article will further explore the pathophysiology of gynecomastia along with the different lines of management.